(untitled) (Ornitología Colombiana, 2021)
We present the first description of the nest and eggs of the Beautiful Jay (Cyanolyca pulchra) found in northwest Pichincha, Ecuador. This corvid is endemic to the Chocó bioregion, it is known from few localities, and is considered globally Near Threatened. The nest was a cup constructed of thin sticks with a lining of fine brown fibers and was decorated externally with moss; it was located 2.5 m above the ground in a dense 4.5 m Clusia tree on a forest edge; the clutch was two eggs, pale green with fine, sparse brownish blotches. The nest and eggs resembled those reported for other Cyanolyca species. Only two adults attended the nest, whereas in the sympatric C. turcosa three adults were observed at a nest. Cyanolyca turcosa may be displacing C. pulchra as deforestation advances. We encourage further study of C. pulchra, especially in its area of sympatry with C. turcosa, to obtain information to aid in its conservation.